Separation of multiple genes controlling the T-cell proliferative response to IL-2 and anti-CD3 using recombinant congenic strains - Lipoldová, M; Kosarová, M; Zajícová, A; Holán, V; Hart, A A; Krulová, M; Demant, P (Immunogenetics, 1995)
T lymphocytes of the strain BALB/cHeA exhibit a low proliferative response to IL-2 and a high response to the anti-CD3 monoclonal antibodies, while the strain STS/A lymphocyte response to these stimuli is the opposite. We analyzed the genetic basis of this strain difference, using a novel genetic tool: the recombinant congenic strains (RCS). Twenty BALB/c-c-STS/Dem (CcS/Dem) RCS were used, each containing a different random set of approximately 12.5% of the genes from STS and the remainder from BALB/c. Consequently, the genes participating in the multigenic control of a phenotypic difference between BALB/c and STS become separated into different CcS strains where they can be studied individually. The strain distribution patterns of the proliferative responses to IL-2 and anti-CD3 in the CcS strains are different, showing that different genes are involved. The large differences between individual CcS strains in response to IL-2 or anti-CD3 indicate that both reactions are controlled by a limited number of genes with a relatively large effect. The high proliferative response to IL-2 is a dominant characteristic. It is not caused by a larger major cell subset size, nor by a higher level of IL-2R expression. The response to anti-CD3 is known to be controlled by polymorphism in Fc gamma receptor 2 (Fcgr2) and the CcS strains carrying the low responder Fcgr2 allele indeed responded weakly. However, as these strains do respond to immobilized anti-CD3, while the STS strain does not, and as some CcS strains with the BALB/c allele of Fcgr2 are also low responders, additional gene(s) of the STS strain strongly depress the anti-CD3 response. In a backcross between the high responder and the low responder strains CcS-9 and CcS-11, one of these unknown genes was mapped to the chromosome 10 near D10Mit14. The CcS mouse strains which carry the STS alleles of genes controlling the proliferative response to IL-2 and anti-CD3 allow the future mapping, cloning, and functional analysis of these genes and the study of their biological effects in vivo.
Keywords: CD3 Complex; druhová specificita; Male; monoklonální protilátky; Chromosome Mapping; Interleukin-2; Lymphocyte Activation; antigeny CD3; myši inbrední BALB C; mužské pohlaví; Species Specificity; Flow Cytometry; aktivace lymfocytů; T-lymfocyty; Mice, Inbred BALB C; průtoková cytometrie; Animals; interleukin-2; ženské pohlaví; mapování chromozomů; zvířata; Recombination, Genetic; rekombinace genetická; myši; T-Lymphocytes; Antibodies, Monoclonal; Mice; Female